Mutagenic activity of water samples from Kaskelen River (Kazakhstan) on plant test systems - Jenisbayeva, Assel; Lovinskaya, Anna; Dauletbayeva, Saniya (BIO web of conferences, 2024)
Rivers are pivotal in the life processes of all living organisms, including humans. The engagement of rivers in daily human economic endeavours has precipitated and continues to precipitate disturbances in the ecological equilibrium, long-established by the forces of evolution. Consequently, providing clean, high-quality water is paramount for sustaining all life forms. This investigation aimed to examine the mutagenic potential of water samples from the Kaskelen River, which is subjected to anthropogenic influences, employing plant-based test subjects. The water’s mutagenic properties were assessed through an assay for chromosomal aberrations (utilizing the metaphase approach) on Hordeum vulgare L. The results demonstrated a statistically significant decline in the mitotic index under all experimental conditions compared to the negative control (p<0.05), indicating the cytotoxic effects of the water samples under study. Further analysis of the water’s mutagenic activity elucidated its capacity to induce structural mutations within the root meristem cells of barley, manifesting a significant uptick in the frequency of chromosomal aberrations relative to the negative control (p<0.05). The extensive array of observed chromosomal rearrangements underscores the existence of mutagenic agents in the river’s water, possessing a broad spectrum of effects.